2019
DOI: 10.3390/jcm8101555
|View full text |Cite
|
Sign up to set email alerts
|

Serial, Visually-Evoked Potentials for the Assessment of Visual Function in Patients with Craniosynostosis

Abstract: This study aimed to evaluate the effect of craniofacial surgical intervention on the visual pathway’s function by comparing pre- to post-operative patterned, visually-evoked potentials (pVEP). A retrospective review was conducted on craniosynostosis patients who had pre- and post-craniofacial surgery pVEP testing. The pVEP measured grade in terms of amplitude latency and morphology of the waveforms. The pre- and post-operative results were compared. The study identified 63 patients (mean age at preoperative pV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Nevertheless, an abnormal PR-VEP at baseline does predict worse visual outcome and shares a close relationship with visual field abnormalities [ 241 , 242 ]. Other studies have demonstrated a high prevalence of PR-VEP abnormality in paediatric craniosynostosis [ 243 ], including the use of serial PR-VEPs in longitudinal monitoring of rICP, some demonstrating a 71% sensitivity and 100% specificity for rICP [ 244 246 ]. These were detected through longitudinal study of PR-VEPs recorded to a range of spatial frequencies, which improves the sensitivity of detecting rICP in craniosynostosis and IIH [ 247 ].…”
Section: Papilloedema and Raised Intracranial Pressurementioning
confidence: 99%
“…Nevertheless, an abnormal PR-VEP at baseline does predict worse visual outcome and shares a close relationship with visual field abnormalities [ 241 , 242 ]. Other studies have demonstrated a high prevalence of PR-VEP abnormality in paediatric craniosynostosis [ 243 ], including the use of serial PR-VEPs in longitudinal monitoring of rICP, some demonstrating a 71% sensitivity and 100% specificity for rICP [ 244 246 ]. These were detected through longitudinal study of PR-VEPs recorded to a range of spatial frequencies, which improves the sensitivity of detecting rICP in craniosynostosis and IIH [ 247 ].…”
Section: Papilloedema and Raised Intracranial Pressurementioning
confidence: 99%
“…Such anomalies could cause impaired functioning of the visual apparatus, as they have been described in the literature for other genetic conditions linked to cranial and cerebral malformations. 32,33 The cause could also be traced to an altered path and/or an extension of the optical pathways beyond the norm. Or the craniofacial malformations could be the primary cause responsible for abnormal ganglion-cell axon myelination, or the lack of integrity of corpus callosum necessary for the development and plasticity of the visual system.…”
Section: Discussionmentioning
confidence: 99%
“…Such anomalies could cause impaired functioning of the visual apparatus, as they have been described in the literature for other genetic conditions linked to cranial and cerebral malformations. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Visual-evoked potentials testing is not a direct measurement of intracranial pressure, but rather measures the integrity of visual pathways, which are affected by intracranial pressure. 49 Early research demonstrated that increased prolongation of the N2 wave latency period correlates with elevated intracranial pressure. 50 A recent study 51 of 13 patients with late presenting craniosynostosis (average age, 5 years) demonstrated abnormal visual-evoked potentials patterns on serial testing in 71.4 percent of patients with confirmed intracranial hypertension.…”
Section: Specific Issues To Addressmentioning
confidence: 99%